Management of Familial Ovarian Teratoma: The Need for Guidance - Sarah Braungart; Majella McCullagh (Georg Thieme Verlag KG, 2016)
Abstract Ovarian teratomas in prepubertal females are uncommon, but familial ones are exceedingly rare. We report an ovarian teratoma in an 8-year-old girl, her mother, and her maternal grandmother. The risk of a metachronous tumor and subsequent complications (such as torsion) in the contralateral ovary remain unclear. There is no clear guidance on follow-up management of patient and family members in the literature. We have reviewed the literature and discuss the challenges for the pediatric surgeon arising from such cases.